Monobenzyl ether of hydroquinone 20 and 40% cream in depigmentation of patients with vitiligo: a randomized controlled trial - Medhat El Mofty; Wedad Z Mostafa; Samia Esmat; Nesrin Samir; Solwan I El-Samanoudy; Marwa S El-Mesidy; Dina G Saadi; Hagar El Sayed; Sarah Ibrahim (Wolters Kluwer Medknow Publications, 2020)
Background Depigmentation represents a final alternative for patients with widespread vitiligo, failing to attain satisfactory pigmentation and having a compromised quality of life. Monobenzyl ether of hydroquinone (MBEH) is the most widely used depigmenting agent, but little is known regarding specific features of its utilization. Objective To evaluate and compare two concentrations of MBEH cream (20 and 40%) regarding their effectiveness, tolerability, and effect on patients' quality of life. Patients and methods In a double-blind randomized study, 40 patients indicated for depigmentation were equally divided into MBEH 20 and 40% groups. Patients' responses were assessed bimonthly over 1 year or till complete depigmentation was attained through photography, point counting, and colorimetric assessment. Baseline and final evaluations by dermatology life quality index and visual analog scale were performed. Patients were followed up for 6 months. The study was registered under number 'PACTR201808699550182.' Results A total of 39 patients completed the study. Significant color dilution, reduction of point counting and melanin indices, and improvement of dermatology life quality index and visual analog scale scores were obtained in both groups. The number of patients who achieved complete depigmentation and the degree of skin irritation was higher in MBEH 40% group, but no significant difference was found regarding the efficacy, adverse effects, or relapse between groups. Conclusion MBEH 20 and 40% concentrations proved to be effective in depigmentation; however, MBEH 20% is more suitable for face in terms of safety profile, whereas MBEH 40% can be employed for resistant cases as well as for hands and areas of thick skin.